Observation of D0→K+π- - CINABRO, D.; et al. (Institutional Knowledge at Singapore Management University, 1994)
Using the CLEO II data sample, with an integrated luminosity of 1.8 fb−1 at and near the Υ(4S) resonance, we have observed a signal for D0→K+π−, which could be due to either D0D¯0 mixing or doubly Cabibbo suppressed decay, or a combination of the two. We find scrB(D0→K+π−)/scrB(D0→K−π+)=0.0077±0 .0025(stat) ±0.0025(syst).